The influence of social media on brand awareness, perceived quality, brand loyalty and purchase intention of smartphones among university students - Mashapa, Tawanda (Vaal University of Technology, 2021)
The evolution of social media has seen people around the world connect with one another, communicate and share information without boundaries and time limitation. Social media is no myth, neither is it just a trend but a powerful communication medium which presents a fundamental shift in communication that cuts across all cultures, be it social, business, politics, sports, news and more. Social media adoption over the years, has seen billions of people participating on social networking sites and the interaction thereof has considerably influenced marketing related correspondence, public relations as well as modern day business communication. In the connected world, social media interaction is the current word-of-mouth, often referred to as electronic word of mouth and in the connected world, everyone is a content generator. In this social media era, information travels faster, reaching millions of consumers and affecting their perception towards certain products and brands based on the information shared and received. Therefore, social media interaction has proved to be an important contributing factor in consumer’s purchase decision process. However, this evolution in communication introduces unprecedented challenges as well as opportunities for organisations as buying decisions are affected significantly by social media interaction, and thus warranties a study of this nature to be carried out. The aim of this study was to examine the influence of social media on brand awareness as well as the relationships between brand awareness, perceived quality, brand loyalty and purchase intention. To attain the empirical objectives of the study, a quantitative research design was adopted and the respondents were selected using a non-probability convenience sampling technique. For data collection, the researcher used a structured self-administered questionnaire survey. Of the 320 distributed questionnaires, the researcher utilised 304 usable questionnaires for data analysis. The Statistical Package for Social Sciences (SPSS) version 25.0 was used to compute both descriptive and inferential statistics (which includes correlation and regression analysis). In addition, the reliability and validity analysis were carried out in relation to the measuring instrument. Results from the correlation and regression analysis revealed positive significant relationship between social media and brand awareness, brand awareness and perceived quality, brand loyalty and purchase intention, perceived quality with brand loyalty and purchase intention as well as brand loyalty and purchase intention. Based on the results of the study, recommendations emanating from the study include the integration of social media marketing in the organisation’s overall marketing strategy, creating and maintaining online brand communities to engage with current and potential customers as well as making use of social media platforms for advertising and promotions. The limitations of the study and the proposed opportunities for further research were also highlighted.
M. Tech. (Department of Marketing Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Social media; Brand awareness; Brand loyalty; Perceived quality; Purchase intention; Smartphones; Dissertations, Academic -- South Africa.; Social media.; Internet marketing.; Mobile commerce.; Mobile communication systems.; Branding (Marketing).